PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA TENAGA PENDIDIK DAN TENAGA KEPENDIDIKAN DI SMP NEGERI 2 MERBAU MATARAM KABUPATEN LAMPUNG SELATAN - Rosidah Rosidah; Anwar Anwar; Agus Riyanto (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2022)
Education is the basic capital to create superior human resources (HR). The school is one of the alternative educational institutions. Teachers are one of the human resources (HR) in the school. The performance of teachers in schools has an important role in achieving school goals. Performance issues are in the spotlight of many parties, the government's performance will be felt by the community and the performance of teachers will be felt by students or parents. The success of school achievement is determined by various factors, including the leadership of the principal. The principal's leadership provides both mental and moral guidance for educators and education staff and also supervises, as well as records activities. Good communication will create ideas and innovations in increasing teacher work productivity and student learning outcomes. Another factor that can improve teacher performance is motivation. A teacher can work professionally if in himself there is high motivation. The Principal's leadership is a motivator for self-adherence to the teacher's work discipline. Although discipline is one part of the characteristics of teacher performance. Therefore, it is considered necessary to conduct research regarding the leadership role of the principal in improving the performance of educators and education staff. The formulation of this research problem is generally how the role of the Principal in improving the performance of educators and education staff. This research is qualitative and aims to find out how the role of the principal in improving the performance of educators and education staff. The principal acts as an educator, manager, administrator, supervisor, leader, innovator, and motivator. To achieve this role the leader must also be able to be a leader in a personal role, a leader in making decisions, and the role of the leader as a source of information. Based on the results of this study, it can be stated that the leadership role of the principal is needed in improving the performance of educators and education staff. Keywords: Leadership, Head-Master, Teacher Performance